Literacy, Financial Inclusion And MSME Business Performance: The Role Of Education Level And Community As Moderators - Khusna, Nur Hidayatul; Setiawan, Doddy (Universitas Muhammadiyah Pontianak, 2025)
This research investigates how financial knowledge and access to financial services impact the business performance of Micro, Small, and Medium Enterprises (MSMEs), while exploring the moderating roles of education level and MSMEs community engagement. The investigation employed a quantitative methodology utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) techniques, gathering information from 140 MSMEs entrepreneurs operating in Kediri, East Java Province. Performance evaluation using Self Assesment Method and Balanced Scorecard.Results demonstrate that financial knowledge and accessibility to financial services generate substantial positive impacts on enterprise performance. Additionally, education background serves as a significant moderator in the relationship between financial accessibility and business performance, whereas MSMEs community engagement amplifies the connection between financial knowledge and business success. Nevertheless, education level did not significantly moderate the financial performance relationship, nor did MSMEs community engagement significantly affect the financial performance connection.These outcomes indicate that importance enhanced access to and comprehension of financial services, based on education level and reinforced through community networks, can strengthen MSME sustainability and market competitiveness. The investigation provides insights for theoretical frameworks and policy development, for stakeholder empowering MSMEs through inclusive and contextually-appropriate financial access enhancement programs.